Market Making Trading Strategy - Čamaj, Matej; Stádník, Bohumil; Fičura, Milan; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2015)
The purpose of this thesis is to analyze market making trading strategy and explore possibilities of using such strategy for intraday trading on the markets with the limit order book. In theoretical part we prove profitability of specified market making strategy under certain assumptions and moreover analyze effect of change of parameters on the performance of the strategy using one dimensional stochastic processes. Next the assumption of constant fair price is relaxed which leads to deterioration of profitability of these strategies. Because one dimensional stochastic processes do not capture price creation in the real world, we propose stochastic model of intraday trading in the next chapter. Advantage of this approach is that we can observe state of the limit order book during whole trading session and therefore better simulate conditions for test of the strategies. Although proposed model exhibit many phenomenons observed in empirical data like volatility clustering, in some situations it produces unrealistically high spread caused by the construction of the model, because arrivals of market and limit orders are modeled as independent processes. Another disadvantages are need of relatively extensive data for model calibration and high sensitivity of model to change of parameters. Lastly we test three different market making strategies under different choice of model parameters and show that expected profitability is positive in all cases.
Vedoucí práce: Bohumil Stádník
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses